Effect of Carbonization Temperature of Charcoal Briquettes from Corn Cob with Gondorukem (Resina Colophonium) Adhesive on Briquette Quality Standards - Johanes Saragih, Kevin; A. Abdullah, Nasruddin; Bahri Widodo, Syamsul (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
Briquettes are an alternative energy source made from agricultural waste. Apart from producing an alternative energy source, briquettes are a more efficient and income-generating solution for processing agricultural waste in Indonesia. This research obtains quality standard of briquettes due to carbonization temperature, time and variations in the ratio of adhesive. Carbonization temperature is 300-350°C, and 350-400°C with a temperature increase rate of 10 °C/minute for 15 and 30 minutes. Then the briquettes are molded with a charcoal mass ratio of 90:10 and 80:20 with adhesive. The briquettes are then tested using the SNI 1683-2021 method including calorific value, water content, ash content, volatile matter and fixed carbon. The best method for this research is Carbonization temperature on 350-400 ℃, time of carbonization and a ratio of 90% raw material and 10% adhesive (90:10) with test results of a heating value of 5,605.75 Cal/g, water content 6.29%, ash content 6.12 %, volatile matter 11.96 % and bound carbon 81.92 %.